2020
DOI: 10.1101/2020.03.03.975672
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteomics Reveals Extracellular Matrix Injury in the Glomeruli and Tubulointerstitium of Kidney Allografts with Early Antibody-Mediated Rejection

Abstract: Antibody-mediated rejection (AMR) accounts for >50% of kidney allograft losses. AMR is caused by donor-specific antibodies (DSA) against HLA and non-HLA antigens in the glomeruli and the tubulointerstitium, which together with inflammatory cytokines such as tumor necrosis factor alpha (TNFα) and interferon gamma (IFNɣ), trigger graft injury. Unfortunately, the mechanisms governing cell-specific injury in AMR remain unclear. We studied 30 for-cause kidney biopsies with early AMR, acute cellular rejection or acu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 91 publications
2
1
0
Order By: Relevance
“…The maladaptive response may lead to chronic antibody-mediated rejection, which pathologically manifests as transplant glomerulopathy, peritubular capillary basement membrane multilayering and arterial intimal fibrosis [21]. A recent work by Clotet-Freixas demonstrated a significant decrease in ECM proteins in glomeruli and tubulointerstitium [13]. Accordingly, our findings showed the elevation of MFAP5 and the reduction of MXRA8 and Cadherin-2 in the urine profile of AR patients.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The maladaptive response may lead to chronic antibody-mediated rejection, which pathologically manifests as transplant glomerulopathy, peritubular capillary basement membrane multilayering and arterial intimal fibrosis [21]. A recent work by Clotet-Freixas demonstrated a significant decrease in ECM proteins in glomeruli and tubulointerstitium [13]. Accordingly, our findings showed the elevation of MFAP5 and the reduction of MXRA8 and Cadherin-2 in the urine profile of AR patients.…”
Section: Discussionsupporting
confidence: 59%
“…In our previous investigation on biomarker discovery in AMR patients, we observed that ECM proteins including collagens and nidogen-1 downregulated in urine profile [12]. Proteomics study on glomeruli and tubulointerstitial revealed downregulation of collagens, nidogen and laminin subunits and elevation of ECM proteolytic enzymes in AMR patients [13]. In this study, we found that ECM degradation progression and EMT signaling factors (MFAP5, MXRA8, Cadherin-2, SAA and EGF) changed in acute rejection.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation